Case report: Compartment syndrome secondary to a snakebite; To cut or not to cut? - Marwa Al-Azzawi; Ammar J.K. Al-Azzawi (Elsevier, 2016)
Compartment syndrome, once diagnosed is almost always followed by a decision of fasciotomy, here we present a case of compartment syndrome which turned out to be secondary to a snakebite and where prophylactic fasciotomy is not considered in such a case as discussed in literature.